An Examination of Banjar Ethnic Marriage Customs From A Living Hadith Perspective: Telaah Perkawinan Adat Banjar dari Perspektif Living Hadis - Hanafi, Hanafi; Dzikri Nirwana (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The assimilation of local culture with Islamic values continues to expand in various lines of Muslim life in the archipelago, especially in the Banjar community. One can be seen in the Banjar marriage tradition as a series of events. The tradition continues to be implemented and preserved by the local community. This research aims to trace further the process of cultural assimilation and its intersection with the prophet's hadith. Two questions form the basis of the study: first, what is the process of involvement of the hadith (sunnah) in shaping the customs that have taken root in the community; second, what is the process of contextualization of the hadith text into the local context of the Banjar community?. The results show that the marriage custom, which was a local culture, has sunnah values that can then become a medium for the perpetrators to gain rewards and blessings. In addition, the universal values of hadith can also be applied in the form of hadith's contextualization that is local culture.